Religious Holiday Allowance as a Form of Justice for Casual Workers in Indonesia - I Putu Sukadana; Wiwik Afifah (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Wage regulations are designed with the main objective of protecting the welfare of workers and providing a sense of justice for all workers. One form of wage that is a right for workers in Indonesia is the provision of Religious Holiday Allowance as non-wage income. The implementation of the provision of Religious Holiday Allowance has several problems such as being underpaid, not paid, paid late, and paid in installments as much as possible. In addition, there are also gaps and legal issues for casual workers with work intensity below 21 working days in a month and who have worked for more than 3 consecutive months, so they do not get Religious Holiday Allowance. The purpose of writing this journal is to analyze the regulation of the provision of Religious Holiday Allowance to casual workers under existing positive laws in Indonesia. The writing of this journal uses the normative juridical method through conceptual and statutory approaches. Based on the analysis that has been done, it shows that the Religious Holiday Allowance for casual workers who work with a working period of more than or less than 12 months and or work not full for 21 working days in a month, can cause legal problems due to unclear calculations so that the impact is not paid Religious Holiday Allowance. The sanctions for employers who do not pay Religious Holiday Allowance on time are fines and administrative sanctions. However, many casual workers do not settle the dispute, both litigation and non-litigation, due to the need for work in addition to the unequal position in the employment agreement.